Rediscovering wild food to diversify production across Australia's agricultural landscapes - Canning, Adam D. (Frontiers in Sustainable Food Systems, 2022)
Conventional agriculture currently relies on the intensive and expansive growth of a small number of monocultures, this is both risky for food security and is causing substantial environmental degradation. Crops are typically grown far from their native origins, enduring climates, pests, and diseases that they have little evolutionary adaptation to. As a result, farming practices involve modifying the environment to suit the crop, often via practices including vegetation clearing, drainage, irrigation, tilling, and the application of fertilizers, pesticides, and herbicides. One avenue for improvement, however, is the diversification of monoculture agricultural systems with traditional foods native to the area. Native foods benefit from evolutionary history, enabling adaptation to local environmental conditions, reducing the need for environmental modifications and external inputs. Traditional use of native foods in Australia has a rich history, yet the commercial production of native foods remains small compared with conventional crops, such as wheat, barley and sugarcane. Identifying what native crops can grow where would be a first step in scoping potential native food industries and supporting farmers seeking to diversify their cropping. In this study, I modeled the potentially suitable distributions of 177 native food and forage species across Australia, given their climate and soil preferences. The coastal areas of Queensland's wet tropics, south-east Queensland, New South Wales, and Victoria were predicted to support the greatest diversity of native food and forage species (as high 80–120 species). These areas also correspond to the nation's most agriculturally intensive areas, including much of the Murray-Darling Basin, suggesting high potential for the diversification of existing intensive monocultures. Native crops with the most expansive potential distribution include Acacia trees, Maloga bean, bush plum, Emu apple, native millet, and bush tomatoes, with these crops largely being tolerant of vast areas of semi-arid conditions. In addition to greater food security, if diverse native cropping results in greater ecosystem service provisioning, through carbon storage, reduced water usage, reduced nutrient runoff, or greater habitat provision, then payment for ecosystem service schemes could also provide supplemental farm income.